2023
DOI: 10.1155/2023/9192494
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Mechanisms Underlying the Gastroprotective Effect of Menthofuran on Experimentally Induced Gastric Lesions in Rodents

Abstract: Menthofuran is a monoterpene present in various essential oils derived from species from Mentha genus, and in Brazil, those species are widely used in treating gastrointestinal and respiratory disorders. Considering the wide pharmacological potential of monoterpenes, including their antioxidant activity, this study aimed to evaluate menthofuran-gastroprotective activity, as well as the involvement of antioxidant mechanisms in this effect. The acute toxicity was evaluated according to the fixed dose method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Menthol had its antispasmodic [ 18 , 19 ] and gastroprotective [ 20 ] activities previously investigated, whereas isomenthone showed protective activity against tumor necrosis factor- α –induced cell death [ 21 ]. Interestingly, a previous study has reported the menthofuran-induced gastroprotective effect by underlying antioxidant mechanisms [ 22 ]. Besides, since any study regarding the effects of menthofuran in the gastrointestinal motility, the present study aimed to investigate menthofuran-induced effects in the gastrointestinal motility by using in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Menthol had its antispasmodic [ 18 , 19 ] and gastroprotective [ 20 ] activities previously investigated, whereas isomenthone showed protective activity against tumor necrosis factor- α –induced cell death [ 21 ]. Interestingly, a previous study has reported the menthofuran-induced gastroprotective effect by underlying antioxidant mechanisms [ 22 ]. Besides, since any study regarding the effects of menthofuran in the gastrointestinal motility, the present study aimed to investigate menthofuran-induced effects in the gastrointestinal motility by using in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 99%